Aspect-ratio Dependence of Optical Nonlinearities on Resonance with Longitudinal Surface Plasmon in Au Nanorods: Unique Character versus Common Behavior - Hendry I. Elim; Wei Ji; Mohan Singh Dhoni; N. Venkatram; Jian Yang; Jim Yang Lee (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2018)
Unique character and common behavior are two distinguished things. In frontier nanoscience and nanotechnology, unique characters were normally obtained in some novel exotics materials such as metal-metal core-shell materials, metallic-semiconducting hybrid nanomaterials, and organic-inorganics complex nano-compounds. On the other hand, normal behavior of natural phenomena including in nano-size objects were obviously predicted based on their exact size related to confinement effect, and capability to interact with another physical system in nature. Here, we report an example of unique character due to evolution nonlinear behavior observed in gold nanorod with their aspect-ratio dependence of optical nonlinearities investigated by femtosecond Z-scan measurements closed to resonance longitudinal surface plasmon peak in gold nanorods (Au NRs). Saturable absorption manifests itself at low excitation (laser irradiances < 7.0 GW/cm2), while reverse saturable absorption dominates at higher excitation. Both the nonlinear processes are found to increase with the aspect ratio of Au NRs. Based on the discrete dipole approximation, qualitative explanations are presented for the observed nonlinear behavior. While common behavior in metallic quantum dots or other shapes of metallic nanomaterials was not the significant in our observation.